97 Men and Women differ in their Adaptation to Aortic Stenosis and in Reverse Remodelling following Aortic Valve Intervention. (6th June 2015) - Dobson, Laura; Musa, Tarique; Uddin, Aklaque; Blackman, Daniel; Fairbairn, Timothy; Swoboda, Peter; Erhayiem, Bara; Ripley, David; McDiarmid, Adam; Garg, Pankaj; Plein, Sven; Greenwood, John
Abstract : Background: Outcomes following aortic valve intervention may differ according to gender. It has been suggested that men and women adapt differently to aortic stenosis (AS) but the effect of gender on left ventricular (LV) remodelling following valve intervention is not well described. We sought to establish using cardiac magnetic resonance (CMR) imaging, the reference standard non-invasive technique for the assessment of LV mass (LVM) and function, whether there was any difference between genders in LV remodelling in severe AS at baseline and reverse remodelling six months following aortic valve intervention. Methods: 100 patients (60 men) with symptomatic severe AS undergoing surgical or percutaneous aortic valve intervention were prospectively recruited between April 2009 and March 2014. Patients with contraindications to CMR were excluded and all patients provided informed written consent. All patients underwent an identical 1.5T CMR protocol (Intera, Philips) prior to and at a median of 6 months following aortic valve intervention (IQR 5–6 months). Multi slice, multiphase imaging was carried out using a standard steady-state free procession pulse sequence in axial and short axis to cover the entire left heart. Quantitative analysis was performed using dedicated computer software (CVI42, Circle Cardiovascular Imaging, Alberta, Canada). Results: Basic demographic, clinical and echocardiographic data can be seen in Table 1 . Women were older than men but were similar in terms of co-morbidity, surgical risk and valvular haemodynamics. At baseline, women had lower indexed LVM (LVMi) than men and a smaller indexed LV end diastolic volume (LVEDVi). Baseline LV ejection fraction (LVEF) and indexed left atrial volume (LAVi) were similar between sexes. Following valvular intervention, LVMi was significantly reduced in both sexes, however, this was more marked in men (18.28 ± 10.63 vs 12.69 ± 8.84, p = 0.007). There was an improvement in LV longitudinal function and a decrease in LAVi in men but not in women. Neither group experienced a significant change in LVEF following intervention (men 54.84 ± 12.94% to 56.52 ± 10.50%, p = 0.093; women 58.61 ± 10.57 to 60.20 ± 11.00, p = 0.129). Both groups also experienced a significant reduction in LVEDVi following valve intervention, with a trend towards a more pronounced reduction in men (men 11.55 ± 20.31 ml/m 2 vs women 5.39 ± 14.10 ml/m 2, p = 0.141). Conclusion: Men and women with AS remodel differently with more hypertrophy and larger LV cavity size in men. Six months following valvular intervention, men but not women experience an improvement in LV longitudinal function and a decrease in left atrial size. These surrogate markers of a reduced left atrial pressure may be accounted for by the greater magnitude of LVM regression seen in men.